2020
DOI: 10.1007/s43037-019-00011-7
|View full text |Cite
|
Sign up to set email alerts
|

Hardy and Rellich inequalities for anisotropic p-sub-Laplacians

Abstract: In this paper we establish the subelliptic Picone type identities. As consequences, we obtain Hardy and Rellich type inequalities for anisotropic p-sub-Laplacians which are operators of the formwhere X i , i = 1, . . . , N , are the generators of the first stratum of a stratified (Lie) group. Moreover, analogues of Hardy type inequalities with multiple singularities and many-particle Hardy type inequalities are obtained on stratified groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In [28] and [29], the (direct) integral Hardy inequalities on metric measure space were established for 1 < p ≤ q < ∞ and 0 < q < p, 1 < p < ∞, respectively, with applications on homogeneous Lie groups, hyperbolic spaces, Cartan-Hadamard manifolds with negative curvature and on general Lie groups with Riemannian distance. Also, on Riemannian manifolds the Hardy inequality was obtained in [31], and on homogeneous Lie groups the Hardy inequality was obtained in [13], [24]- [23] and [30]. In the present paper, we continue the analysis in the general setting of metric measure spaces as in [28] and show the reverse integral Hardy inequality with q < 0 and p ∈ (0, 1).…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…In [28] and [29], the (direct) integral Hardy inequalities on metric measure space were established for 1 < p ≤ q < ∞ and 0 < q < p, 1 < p < ∞, respectively, with applications on homogeneous Lie groups, hyperbolic spaces, Cartan-Hadamard manifolds with negative curvature and on general Lie groups with Riemannian distance. Also, on Riemannian manifolds the Hardy inequality was obtained in [31], and on homogeneous Lie groups the Hardy inequality was obtained in [13], [24]- [23] and [30]. In the present paper, we continue the analysis in the general setting of metric measure spaces as in [28] and show the reverse integral Hardy inequality with q < 0 and p ∈ (0, 1).…”
Section: Introductionmentioning
confidence: 63%
“…By taking the second derivative of k(α) at the point α 1 and by denoting k 23) This means that, function k(α) has supremum at the point α = α 1 . Then, the biggest constant has the following relationship…”
Section: B(a R)mentioning
confidence: 99%
“…The Hardy inequality was intensively studied. For example, the Hardy inequalities were considered on the Euclidean space in [19], [20], on the Heisenberg group in [6], [7], on stratified groups in [3], [31,32,33], [36], [42], for the vector fields in [34] and [38], on homogeneous groups in [37], [39]. In [37] (see e.g., [35]), authors showed the Hardy inequality with radial derivative on homogeneous groups in the following form: Theorem 1.4.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning anisotropic (non-Riemannian) Rellich inequalities, there is a growing literature on inequalities with distance to a point, see e.g. [8,9,11] and references therein, but we are not aware of any results involving the distance to the boundary. To our knowlegde, the best Rellich constant for |∆u| p dx is not known even in the case of a half-space.…”
Section: Introductionmentioning
confidence: 99%